The effect Between Emotional Intelligence and Communicational Skills with Tension Management Strategies in Educational Managers - naser mohammadi ahmad abadi; tahereh Fallahzadeh (Institute of Management fekrenoandish, 2021)
The present study was conducted with the aim of investigating the effect of emotional intelligence and communication skills of Ardakan educational managers, in three levels; primary, junior high, and high schools, in the 2019-2020 academic year, in predicting stress management practices by descriptive method. To this end, all the 98 managers of the above-mentioned community were selected as a sample group and responded to valid questionnaires of Sibria Shring's emotional intelligence (1998) with 0.84 Krunbach Alpha, Barton communication Skills with 0744 Krunbach Alpha, and Robins Stress Management Scale, after the administrative and initial briefing Session. Multivariate regression analysis methods were used in inferential analysis of data, to determine the predictive power of stress management practices by emotional intelligence, communication skills and their components. The findings indicated that emotional intelligence and communication skills and all its components had a significant power of prediction for the criterion variable (stress management) (p>0.05). Based on these results, apparently reinforcement of emotional intelligence and communication skills of managers can play a significant role in promoting the level of stress management practices in educational managers.